Money supply, money demand, and macroeconomic models - Havrilesky, Thomas M.; Boorman, John T. (Arlington Heights, Ill. : H. Davidson, 1982)
This book examine the econometric implications of two alternative theories of the monetary process. Both the neo-Keynesians and the Monetarist see a general portfolio balance mechanism at work in the economy, but agreement seems to stop there. Their divergent views concerning the importance of interest rates, the direction of effect of money on interest rates, the nature of price determination, and the feasibility of representing the adjustment process econometrically have been discussed.
Authors' names in reverse order in 1st ed. 1972.
Includes bibliographical references and index.
usc 31/05/2017
Loans
Keywords: Money supply; Demand for money; Monetary policy; Macroeconomics